P–566 Advanced paternal age can influence aneuploidy rate in egg donation cycles with poor sperm quality. (6th August 2021) - Iovine, E; Zazzaro, V; Pirastu, G; Scarselli, F; Ruberti, A; Paccagnini, D; Colasante, A; Greco, P; Pristerà, A; Varricchio, M T; Caragia, A; Greco, A; et al.
Abstract: Study question: Could advanced paternal age influences the embryos aneuploidy rate in eggs donation cycles with poor sperm quality? Summary answer: In case of severe male factors increased paternal age can affect embryos aneuploidy rate in egg donation cycles. What is known already: While the impact of advanced maternal age on reproductive is well understood, the effect of paternal age on reproductive function is controversial. Many studies have shown that Advanced Paternal Age (APA) could impact on male fertility potential affecting testicular function and sperm quality. Moreover, APA also has been associated with increased epigenetics changes and DNA mutations. Increased paternal age could be associated with different types of disorders such as autism, schizopherenia and bipolar disorders. Egg donation cycles, controlling female variables, represent the ideal model for the study of the impact of paternal age on reproductive outcomes. Study design, size, duration: We retrospectively analyzed 43 egg donation cycles (October 2014-January 2020) with ≥ 50% survival rate of vitrified/warmed oocyte. Only cycles with poor sperm quality were considered. Cycles were divided in two GROUPS: group–1 included male paternal age ≤ 45 while group–2 included male paternal age >45. Data, shown as avarage±SD, were analyzed with Chi square or Student-t test. Participants/materials, setting, methods: Group–1 included 20 cycles and 219 oocytes, male age was 40, 89 ±6.12; Group–2 included 17 cycles and 173 oocytes, male age was 51±6.06. Respectively, in Group 1 and in Group 2, donor age were 22.4±2.65 and 24.8±3.88 (NS). All oocytes were injected with abnormal sperm samples according to WHO 2010. Embryos were cultured in time-lapse system until blastocyst stage. Trophectoderm biopsy and PGT-A analysis were performed according to standardized laboratory protocols. Main results and the role of chance: Oocytes survival rates in Group1 and 2 were 86% (188/219) and 90.7% (157/173) (NS), respectively. Fertilization rates in Group1 and –2 were 71.42 (135/189) and 73.45% (119/162) (NS), respectively. The total number of obtained embryos (transferred + frozen) were 81 and 801 in Group–1 and –2, respectively. The rates of obtained embryos per reiceved occytes were 37% (81/219) and 46.24% (80/173) in Group–1 and –2 (p < 0.7), respectively. The PGT-A analysis showed 38.7% (31/80) and 31.17% (24/77) of euploid (NS) and 25% (20/80)and 42.85% (33/77) of aneuploid embryos (P < 0.05) in Group–1 and –2, respectively. Mosaic embryos were 33.5% (26/80) and 27.27%(21/77), in Group–1 and –2, respectively. (NS). These results indicate that in presence of severe male factor, advanced paternal age could increase embryos aneuploidy rate raising incidence of chromosomal abnormalities. Limitations, reasons for caution: Each donor was stimulated with different protocols according to her history and hormones levels. Nothing is known about which type of sperm parameters (semen amount, morphology or motility) have a major impact when focusing on the embryos genetic outcome. Wider implications of the findings: To better known the effect of APA, it could be necessary identify embryos chromosomal abnormalities and the correlation with specific sperm parameters. Further studies should be done to confirm the APA effect in patients with severe male factors and define a cut-off male age where PGT-A should be recommended. Trial registration number: Not applicable